COVID-19 challenges to equity: Insights from rural Nepal and Senegal - Barooah, Prapti; Wouterse, Fleur; Saini, Smriti; Alvi, Muzna; Ringler, Claudia (United States Agency for International Development, 2020)
Globally, COVID-19 has exposed farmers to high levels of income insecurity, underlining the importance of building resilience among male and female farmers. Female farmers might be particularly vulnerable to COVID-19 impacts due to lower incomes, higher illiteracy, and limited access to resources, time poverty due to increasing domestic and productive responsibilities, and overall patriarchal norms including restrictions on mobility that prevent women from realizing their productive potential.